ANALISIS PERILAKU BELAJAR PESERTA DIDIK PADA MASA PANDEMI COVID-19 TERHADAP MATA PELAJARAN IPS KELAS VIIIB SMP NEGERI 2 BATU AMPAR KABUPATEN KUBU RAYA - Ryan Anditya Desvandira; Aminuyati Aminuyati; F. Y. Khosmas (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
This study aims to determine "student learning behavior during the COVID-19 pandemic towards social studies subjects for class VIIIB SMP Negeri 2 Batu Ampar,Kubu Raya district". This study uses a qualitative method. The data in this study areprimary data and secondary data. The data collection techniques used wereobservation, direct interviews, and documentation studies. While the data collectiontools are observation guidelines, interview guidelines and documentation tools.Informants in this study were class VIIIB students of SMP Negeri 2 Batu Ampar, Kubu Raya Regency. The results of this study indicate that the learning behavior of class VIIIB students of SMP Negeri 2 Batu Ampar, Kubu Raya Regency is good. Students have the habit of being on time, preparing study equipment before the teacher arrives, and are accustomed to reading material both in class and at home. Students have good skills in participating in social studies learning. Students are able to follow the learning actively and carefully. So that it can determine the important things that should be noted. Students are very enthusiastic in participating in social studies lessons. They stated that social studies subjects were very easy to understand.Keywords: Behavior, Learning Behavior, Social Studies